Language, Religion, and Modernity: Zaki Naguib Mahmud's Islamic Rationalism Philosophy - Supriyanto Supriyanto (Tamaddun, 2022)
This article aims to reveal the idea of renewing thought in the minds of Zaki Naguib Mahmud.  The method used in this research is descriptive-qualitative and is included in the literature research. The process of collecting data in this study is by observing, in the sense of tracking various references that have relevance related to the focus of the study, such as his work entitled Qishah al-Falsafah al-hadithah, Qisshah al-Falsafah al-Yunaniyah, Qisshatul Adab fi al-‘Alam as well as from books, articles, and so on which function to support these data. The data analysis technique used in this research is the content analysis method. From the studies conducted, the linguistic revolution is the entrance to renewal. Zaki saw the need for a linguistic revolution. He offers to change from the tradition of words to the practice of work and from words to meaning. The renewal of religious thought offered by Zaki is an epistemological criticism of Islamic religious belief. Zaki invites us to examine and differentiate between Religion, Religious Knowledge, and Religious Thought. For Zaki, religion is sacred and sacred. Meanwhile, religious knowledge and thought are impure; they can be touched and criticized. Islamic thought turath is divided into two, al-Ma‘qul and al-La Ma‘qul. The attention of Muslims to the latter rather than the former and their narrow understanding has caused them to be backward. So serious attention is needed to the ma’qul side of classical Islamic heritage and reinterpreting the meaning of al-La Ma’qul.